Βιβλιοκρισία του: GARY VIKAN, Early Byzantine Pilgrimage Art. Revised Edition (first published 1982). Dumbarton Oaks Byzantine Collection Publications 5, Washington DC: Dumbarton Oaks Research Library and Collection, Trustees for Harvard University, 2011 - YANGAKI, Anastasia G. (Byzantina Symmeikta, 2012)
book review: Gary Vikan, Early Byzantine Pilgrimage Art. Revised Edition (first published 1982). Dumbarton Oaks Byzantine Collection Publications 5, Washington DC: Dumbarton Oaks Research Library and Collection, Trustees for Harvard University pp. 109. ISBN: 978-0-88402-358-6.